Konsep Pendidikan Ukhuwah wathaniyah Perspektif Hadratussyaikh KH. M. Hasyim Asy’ari (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
This article explores the concept of ukhuwah wathaniyah (national brotherhood) as envisioned by Hadratussyaikh KH. M. Hasyim Asy'ari, a prominent Indonesian religious figure. It also examines the critical need for character education for students in the current era. The research employs a literature study method, analyzing Hasyim Asy'ari's works, particularly those collected in "Irsyād as-Sārī Fī Jam'i al-Muṣannafāt asy-Syaikh Hāsyim 'Asy'arī," along with other relevant documents such as manuscript books and his speeches, as well as books about him. An interpretive approach is used to understand the social and historical contexts that influenced Hasyim Asy'ari's thought, in order to unveil his concept of ukhuwah wathaniyah education. The research findings classify Hasyim Asy'ari's concept of ukhuwah wathaniyah education as consisting of politics based on Islam, a spirit of nationalism as the basis of ukhuwah wathaniyah, and a spirit of building unity as the foundation of ukhuwah wathaniyah